Establishment of a knock-in mouse model with the SLC26A4 c.919-2A>G mutation and characterization of its pathology. - Ying-Chang Lu; Chen-Chi Wu; Wen-Sheng Shen; Ting-Hua Yang; Te-Huei Yeh; Pei-Jer Chen; I-Shing Yu; Shu-Wha Lin; Jau-Min Wong; Qing Chang; Xi Lin; Chuan-Jen Hsu (PLoS ONE, 2011)
Recessive mutations in the SLC26A4 gene are a common cause of hereditary hearing impairment worldwide. Previous studies have demonstrated that different SLC26A4 mutations may have different pathogenetic mechanisms. In the present study, we established a knock-in mouse model (i.e., Slc26a4(tm1Dontuh/tm1Dontuh) mice) homozygous for the c.919-2A>G mutation, which is a common mutation in East Asians. Mice were then subjected to audiologic assessment, a battery of vestibular evaluations, and inner ear morphological studies. All Slc26a4(tm1Dontuh/tm1Dontuh) mice revealed profound hearing loss, whereas 46% mice demonstrated pronounced head tilting and circling behaviors. There was a significant difference in the vestibular performance between wild-type and Slc26a4(tm1Dontuh/tm1Dontuh) mice, especially those exhibiting circling behavior. Inner ear morphological examination of Slc26a4(tm1Dontuh/tm1Dontuh) mice revealed an enlarged endolymphatic duct, vestibular aqueduct and sac, atrophy of stria vascularis, deformity of otoconia in the vestibular organs, consistent degeneration of cochlear hair cells, and variable degeneration of vestibular hair cells. Audiologic and inner ear morphological features of Slc26a4(tm1Dontuh/tm1Dontuh) mice were reminiscent of those observed in humans. These features were also similar to those previously reported in both knock-out Slc26a4(-/-) mice and Slc26a4(loop/loop) mice with the Slc26a4 p.S408F mutation, albeit the severity of vestibular hair cell degeneration appeared different among the three mouse strains.